KARAKTERISTIK SISWA ANGGOTA EKSTRAKULIKULER PENCAK SILAT DITINJAU DARI NILAI KARAKTER - Adyanto, Sisworo Putut; Muhajir, Muhajir; Fajriyah, Khusnul (Universitas Slamet Riyadi, 2018)
This study aims to identify the characteristics of students members of the pencak silat extracurricular in terms of character values. This research method is a qualitative descriptive research that describes events or phenomena with data in the form of information in the form of descriptions from Rejosari 03 Public Elementary School Semarang. Research data sources use informants, observation, and documentation. Procedure Data collection used is observation, interviews, questionnaires, and documentation. Observation results prove that the characteristics of pencak silat extracurricular students reach a high category based on 4.4 and 4.5 page 43 graphs. In addition the results of interviews with curricular trainers and homeroom teachers state that following pencak silat extracurricular activities has a positive impact on students. Therefore, it can be concluded that students who are members of pencak silat extracurricular reach a high criterion of 18 character values set by the Ministry of National Education.